(untitled) (Journal of Information Technology and Digital World, 2023)
Virtual Network Computing (VNC) plays a significant role in advanced remote access by allowing users to remotely control another computer or virtual machine over a network connection, and applies to real-world entities. Virtual remote control is the ability to use software with a graphical user interface to remotely operate a computer or virtual machine. One of the key advantages of controlling a virtual remote is that it allows users to interact with the remote system as if they were physically present at the remote location. This research proposes a design of virtual mouse that relies on Hand Gesture Recognition using OpenCV and VNC. It tracks hand movements and recognizes the gestures to perform the mouse tasks. Hand gesture recognition technology uses computer vision algorithms and machine learning techniques to analyse and interpret human hand movements.